PENGARUH MODEL PEMBELAJARAN ROLE PLAYING BERBANTUAN MEDIA VIDEO ANIMASI TERHADAP KETERAMPILAN BERBICARA SISWA - Galandjindjinay , George Maikel Sefnat; Ansoriyah, Siti; Rohman, Saifur (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Research This study aims to analyze students' speaking skills through a role-playing learning model assisted by animated video media. This study is experimental quantitative research with a One Group Pretest-Posttest Design. The population in this study is all grade VII students of SMP Negeri 5 Benjina, but the selected research sample is class VII-B students with a total of 28 people, and the sampling technique used is non-probability sampling. Data collection in this study is through observation, interviews, tests and documentation. The data analysis techniques used are descriptive and inferential statistical analysis and the Paired Sample T-Test test assisted by the IBM SPSS application to test hypotheses. Based on the results of the research and discussion, it was concluded that there was an influence of the role-playing learning model assisted by animation video media on students' speaking skills. This is evidenced by obtaining an average score of 62.46 for the pre-test and an average score for the post-test of 79.89 which means an average increase of 17.43. These findings are also expected to influence education policies to introduce more varied learning methods, especially in schools located in remote areas.